Fragmented QRS for Risk Stratification in Patients Undergoing First Diagnostic Coronary Angiography - Eyuboglu,Mehmet (2016)
Abstract Background: Only a small proportion of patients referred for coronary angiography with suspected coronary artery disease (CAD) have the diagnosis of obstructive CAD confirmed by the exam. For this reason, further strategies for risk stratification are necessary. Objective: To investigate the relationship of the presence of fragmented QRS (fQRS) on admission electrocardiogram with angiographically detected CAD and CAD severity in patients without known vascular diseases and myocardial fibrosis, undergoing first diagnostic coronary angiography. Methods: We enrolled 336 consecutive patients undergoing coronary angiography for suspected CAD. The patients were divided into two groups according to the presence or absence of fQRS on admission. We compared the groups regarding the presence and severity of CAD. Results: Seventy-nine (23.5%) patients had fQRS on admission. There was not a statistically significant difference between patients with fQRS (41.8%) and non-fQRS (30.4%), regarding the presence of CAD (p = 0.059). However, there was a statistically significant difference between patients with fQRS and non-fQRS regarding the presence of stenotic CAD (40.5% vs. 10.5%, p<0.001) and multi vessel disease (25,3% vs. 5.1%, p<0.001). The frequency of fQRS was significantly higher in patients with SYNTAX score >22 compared to patients with SYNTAX score ≤22. Conclusions: Our findings suggest that fQRS may be an indicator of early-stage myocardial damage preceding the appearance of fibrosis and scar, and may be used for risk stratification in patients undergoing first diagnostic coronary angiography